Association of Serum 25(OH) D Levels with Gestational Hypertension and Risk of Pre-eclampsia in Our Population - Noor-Ul-Ain Ainee, Uzma Malik, Aatka Nisar, Hafiza Haleema Abid, Samina Naz, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Pre-eclampsia is a syndrome of immune system of pregnant females, which causes severe obstetrical complications. Low serum level of 25-hydroxyvitamin-D is common during pregnancy complicated with preeclampsia but local evidence is missing. Aim: To determine the association of pre-eclampsia with decreased vitamin- D levels during two phases of gestation (after 20 weeks) over a period of six months. Study design: Cohort study Place and duration of study: Department of Obstetrics and Gynaecology, Lady Willingdon Hospital, Lahore from 4th February 2019 to 3rd August 2019. Methodology: One hundred and seventy females were enrolled in study at 20 weeks gestational age. They were divided into two groups (85 patients in each group). Those with normal Vitamin D3 levels (>30 ng/ml) were grouped as Low risk group and those with relatively low (insufficient) serum vitamin D3 levels (between 21-29 ng/ml) were grouped as high-risk group with potential risk factor for pre-eclampsia. Both groups were followed from 24+1 weeks to 36 weeks of gestation with every two weeks’ interval, for assessment of development of pre-eclampsia or not. Both groups were followed up and outcome was noted. Results: The mean age of the patients was 26.44±4.08 years and mean gestational age was 35.47±2.34 weeks. One hundred and 42(83.53%) patients appeared with PIH while 28(16.47%) patients appeared with preeclampsia. Among high risk patients, preeclampsia was noted in 26(30.6%) patients while in low risk group patients, preeclampsia was noted in 2(2.4%) patients (p<0.001). Conclusion: A significant association observed between pre-eclampsia and decreased vitamin D level during phases of pregnancy. Keywords: Vitamin D level, Preeclampsia, Hypertension